Methods of Estimating Operative Risks in Trade - G. P. Fomin; I. V. Sukhorukova; V. A. Mushrub (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with Russian retail trade. Today it is very topical due to our economy digitalization and sanctions introduced by some foreign countries. The authors study methodological approaches to the analysis of operative risks in trade and search for risk estimation models in operations of order shaping for the product range, payment, acquisition, transportation, damage, storage and product sale. The conceptual model of researching operative risks in trade was put forward and methodological substantiation of summarized methods and models was given. They are useful for direct application in estimating operative risks in practice, such as those connected with foreign currency, inflation, interest rate, transportation, damage and loss of products and missed profit. The authors give practical examples of using the groups of formal methods of risk estimation in wholesale operations dealing with purchase and sale of foot ware by big retailers. Practical importance of the research results is connected with the opportunity to use these models for operative risk estimation, which could cut losses and minimize risks, avoid unfavourable economic after-effects in the work of Russian retailers.